Factors affecting the career choices of graduating students and graduates of years 2014-2016 of the University of the Philippines College of Pharmacy - Enriquez, Raissa Clarisse M.​; Fensantos, Rei Alexa D.; Moreno, Pia Mae S.​ (2017)
In healthcare, pharmacists play an important role that branches out into several fields of practice. The profession continues to progress, creating more career opportunities. This study focused on assessing the career choices of graduating students and graduates of years 2014-2016 by determining the factors that affect them through a survey questionnaire. For graduates who are working their job satisfaction was also explored. The participants answered a 48-item online survey questionnaire which includes identifying their preferred career, and describing the factors that influence them. The results revealed that the most important factors that influence the career choices were salary (4.12 ± 1.39) and interest in the pharmacy profession (4.12 ± 1.69) while the most preferred career was public health pharmacy (5.25 ± 1.72). Graduating students prefer careers in both hospital (5.33 ± 1.78) and public health pharmacy (5.54 ± 1.71). While non-working participants opt to practice in the hospital setting (5.23 ± 1.85), those who currently have a job prefer careers in the academe (5.17 ± 2.20). Furthermore, it was found that varying factors affect different career choices. Males were more inclined to work in the academe (5.50 ± 2.11), while females prefer to practice in the industry (5.51 ± 2.05) and hospital (5.23 ± 1.94). Those who prefer community pharmacy practice was revealed to be influenced by age (p=0.0237), planned marital status (p=0.0051), year of graduation (p=0.0021), and internship experience (p=0.0000). It was also observed that BS Pharmacy participants were more inclined to work in the fields of hospital pharmacy (5.52 ± 2.02) and medicine (5.10 ± 2.79) while those under BS Industrial Pharmacy, opt to work in the industry (6.35 ± 1.89). Parents (68.72%) were discovered to have the most influence in the preferred career. Moreover, among the working participants, only 25.76% were dissatisfied on their current career, most of whom are in the academe (44%). The study demonstrated that career choice can be influenced by several factors, allowing opportunities to promote the profession across different fields of practice. The results entail the college to encourage the students to consider careers in the least preferred fields of pharmacy practice, revise the curriculum and revisit RSA policies.